Development of ultra high strength concrete based on locally available materials and silica fume - Ng, Wan Chi (Universiti Malaysia Sarawak, UNIMAS, 2010)
The results of an experimental study on developing ultra high strength concrete based on locally available materials and silica fume are presented. Materials used to form ultra high strength concrete mixture were silica fume and superplasticizer as admixture to help the concrete gain the strength needed. The cement was replaced with 0%, 10%, 15% and 20% of silica fume. The hardened concrete properties were tested at the ages of 28 and 56 days. The total cement content selected was 600 kg/m3 for the UHSC. The coarse aggregate used was 14 mm crushed granite with an amount of 60% by weight of total aggregate in concrete. The water cementitious materials ratio equal to 0.21 was chosen. Flow test were conducted to measure the workability of the concrete and also to determine the suitable dosage of superplasticizer. Slump tests were conducted mainly to see the uniformity of the concrete, but not to measure the workability of the concrete. Finally, the compression tests for concrete cube and flexural tests for the concrete beam were performed to determine the compressive strength and the flexural tensile strength of the concrete. The experimental results show that every of the designed mix proportion has achieved the required strength of ultra high strength concrete of higher than 100 MPa.